Electrospun Nanofiber Composites for Drug Delivery A Review on Current Progresses - Renatha Jiffrin; Saiful Izwan Abd Razak; Mohamad Ikhwan Jamaludin; Amir Syahir Amir Hamzah; Muadz Ahmad Mazian; Muhammad Azan Tamar Jaya; Mohammed Z. Nasrullah; Mohammed Majrashi; Abdulrahman Theyab; Ahmed A. Aldarmahi; Zuhier Awan; Mohamed M. Abdel-Daim; et al. (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA